2018
DOI: 10.1053/j.ajkd.2018.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Biological Variability of Estimated GFR and Albuminuria in CKD

Abstract: eGFR markers appear to have relatively low short-term within-person variability, whereas variability in albuminuria appears to be high, making it difficult to distinguish random variability from meaningful biologic changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 34 publications
(30 reference statements)
6
41
0
Order By: Relevance
“…In an uncontrolled operational clinical environment, it is likely that biological and analytical variation, and hence RCVs, would increase. The within-subject biological variation of serum creatinine we have observed (4.4%) is in broad agreement with values reported in other studies in both healthy (4.1% to 7.6%, 16,[21][22][23][24][25][26][27][28] ) and diseased (5.7% to 9.9% 23,[29][30][31] ) cohorts. Enzymatic creatinine methods are less prone to interference than Jaffe methods and the use of an enzymatic assay in the present study improves confidence in the estimate of biological variation we have reported.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In an uncontrolled operational clinical environment, it is likely that biological and analytical variation, and hence RCVs, would increase. The within-subject biological variation of serum creatinine we have observed (4.4%) is in broad agreement with values reported in other studies in both healthy (4.1% to 7.6%, 16,[21][22][23][24][25][26][27][28] ) and diseased (5.7% to 9.9% 23,[29][30][31] ) cohorts. Enzymatic creatinine methods are less prone to interference than Jaffe methods and the use of an enzymatic assay in the present study improves confidence in the estimate of biological variation we have reported.…”
Section: Discussionsupporting
confidence: 92%
“…Although calculation of CV I excludes any contribution due to CV A , it cannot account for biological variability of non-creatinine chromogens (e.g., bilirubin, glucose, ketones, protein, and certain drugs) that are known to interfere in Jaffe methods of creatinine measurement. Similarly, our reported within-subject biological variation of cystatin C (4.0%) is similar to most (3.1%, 32 4.1%, 25 4.5%, 16,27 and 4.8% 29 ) but not all (6.8%, 28 8.6%, 23 and 13.3% 24 ) previous estimates. As for measured GFR, differences in study design and data analysis may account for differences in reported estimates of variation; for example, most of these studies did not report their approach to outlier detection; the time interval between repeat sampling was prolonged in some studies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…At the EDIC study visit when uAOG was increased the AER was also increased and although the eGFR was above 60 mL/ min per 1.73 m 2 in both groups it was already slightly lower in cases than in controls. Of note, the within-person variability of albuminuria is very high as recently shown by Waikar et al (2018). It would therefore be of interest to examine the variability of AOG in longitudinal studies with multiple samples over time.…”
Section: Discussionmentioning
confidence: 90%
“…To the contrary, renal tissue has a more complicated cellular organization due to concomitant presence of different subtypes of cells with unique function such as the glomerular, mesangial, tubular and interstitial cells. Hence, changes in serum creatinine could be the end result of several patho-physiological clinical conditions such as hypovolemia with reduced renal blood flow, nephrotoxic drugs, glomerular and interstitial diseases, sepsis, toxins and obstructive nephropathy (2).…”
mentioning
confidence: 99%